Preparation, Structure‐Performance Relationship, and Reaction Network of ZnZSM‐5 for Oxidative Dehydrogenation of Ethane with CO2. Issue 22 (13th March 2023) - Liu, Pengyu; Zhang, Lina; Wang, Xingbo; Du, Meng; Hao, Yingdong; Li, Lina; Chen, Xinqing; Sun, Nannan; Wei, Wei
Abstract: Ethylene (C2 H4 ) is a major chemical for the modern society, and new technologies for its production are of strategic importance globally. Recently, oxidative dehydrogenation of ethane (C2 H6 ) using CO2 as a milder oxidant (CO2 ‐ODH) is proposed as a potential way for C2 H4 production, and development of effective catalysts for the process is drawing wide attention. Here, we report on a facilely prepared ZSM‐5 supported Zn system, i. e., ZnZSM‐5, which showed great promise in CO2 ‐ODH. Samples with different Zn loadings were prepared and evaluated, and the highest performance was obtained over 0.05ZnZSM‐5 at 700 °C and a CO2 :C2 H6 feeding ratio of 5 : 1. During 340 min TOS, the C2 H6 conversion decreased moderately from 36.2 % to 23.1 %, and the C2 H4 yield stabilized at 21.9 % to 27.9 %. Based on systematic characterization and investigation of reaction conditions, the structure‐performance relationship and reaction network were discussed in detail. Abstract : Indirect oxidative dehydrogenation : Introduction of appropriate amount of Zn onto ZSM‐5 zeolite resulted in highly dispersed and active site for oxidative dehydrogenation of ethane (C2 H6 ) using CO2 as a milder oxidant (CO2 ‐ODH), structure‐performance relationship and reaction network were systematically investigated.